2016
DOI: 10.1002/adfm.201601476
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mechanical Interactions by Local Piezoelectric Effects

Abstract: Piezoelectricity is a well-established property of biological materials, yet its functional role has remained unclear. Here, we demonstrate a mechanical effect of piezoelectric domains resulting from collagen fibril organisation, and describe its role in tissue function and application to material design. Using a combination of scanning probe and nonlinear optical microscopy, we observed a hierarchical structuring of piezoelectric domains in collagen-rich tissues, and explored their mechanical effects in silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…PFM images of soluble collagen films reveal worm-like structures which possess topographical correlation with the lateral amplitude and in phase of the piezoelectric response, unlike its insoluble collagen counterpart. This indicates that although the origin of piezoelectricity may be attributed to the ordering and charge imbalance of tropo collagen molecules, the large piezoelectric domains as observed in tendon 11 may be promoted by the crosslinking of the fibrils into large ordered structures. This is confirmed by previous reports on the piezoelectricity of evaporated and electrodeposited mono-meric collagen films, which reveal that although evaporated films do not exhibit any strong fibrillar elements, they exhibit a small piezoelectric response when imaged using transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PFM images of soluble collagen films reveal worm-like structures which possess topographical correlation with the lateral amplitude and in phase of the piezoelectric response, unlike its insoluble collagen counterpart. This indicates that although the origin of piezoelectricity may be attributed to the ordering and charge imbalance of tropo collagen molecules, the large piezoelectric domains as observed in tendon 11 may be promoted by the crosslinking of the fibrils into large ordered structures. This is confirmed by previous reports on the piezoelectricity of evaporated and electrodeposited mono-meric collagen films, which reveal that although evaporated films do not exhibit any strong fibrillar elements, they exhibit a small piezoelectric response when imaged using transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, when combined in hamstrings, fibrils of opposing polarity are electrostatically attracted to one another and result in a shear piezoelectric response from charge accumulation, whereas those with similar polarity repel, which can result in different mechanical behaviours by facilitating or inhibiting the slipping of fibrils. 11 This slipping behaviour has also been investigated in the 'rough' ultrastructure of biopolymers, including collagen fibrils, where the slipping corresponds to the fibril D-spacing and is suggested to play a role in the toughness of the materials. 12 Advanced atomic force microscopy techniques have seen an improvement in both the ability to characterise materials at unprecedented resolutions as well as the ability to map electromechanical properties of the material onto the topographical features across the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these results could be considered in the design of the dimer and trimer bio‐piezoelectric crystals for future piezoelectric applications. The quantitative analysis of piezoelectricity on collagen fibrils has also been performed using resonance measurement and the PFM method 132–139. In 1999, Goes et al reported the collagen films extracted from bovine serosa exhibit piezoelectric charge coefficient d 14 of 0.096 pC N −1 , measured by the resonance measurement method 140.…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 99%
“…Collagen molecules are parallel-aligned into fibrils and become mineralized to form the extracellular matrix of bone 18 , 19 . Namely, due to the piezoelectricity of collagen fibrils, the extracellular matrix of bone can be pictured as parallel interspersed domains of fibrous piezoelectric collagenous materials and non-piezoelectric non-collagenous materials, resulting in the spatially specific positive charges localized on the collagenous domains ( Figure 1 a ) 20 . In addition, it is proposed that an external electrical cue, though not arising from piezoelectricity, can modulate stem cell behaviors 21 - 24 .…”
Section: Introductionmentioning
confidence: 99%